MENINGKATKAN AKTIVITAS DAN KETERAMPILAN BERPIKIR KRITIS MENGGUNAKAN MODEL PE MANCHING PADA PESERTA DIDIK KELAS IV - Nahdia, Annisa; Riandy Agusta, Akhmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The problem in this research is the low level of activity, critical thinking skills, and lack of understanding of students' material concepts in learning. An attempt to overcome this problem is by using the PE MANCHING model. The research objectives are to describe activities, analyze activities, discipline character and critical thinking skills and improve learning outcomes. The type of research used by PTK. The research subjects were class IV-A students at SDN Teluk Tiram 2 in 3 meetings. Data analysis in this research uses descriptive analysis techniques displayed using tables, graphs and interpretation with percentages. The results of this research show that the teacher's activity at the first meeting only reached a score of 22, at the third meeting it increased to 33, then student activity increased, which at the first meeting only reached 25%, at the third meeting it increased to 90%. Critical thinking ability at meeting I reached 30%, at meeting III it increased to 85%. Classical completeness of learning outcomes at meeting I only reached 20% and increased at meeting III to 100%.